'Identity containers' in nineteenth-century Italy and Germany: an introduction. Issue 4 (7th August 2020) - Caruso, Amerigo; Späth, Jens
ABSTRACT: This special issue reconsiders the process of nation-building in nineteenth-century Italy and Germany before nationalism formed, for the majority of people, the dominant group identity. We will argue that non-national 'identity containers' and their interplay with emerging nationalism were essential for the creation of patriotic sensibilities among Italians and Germans, both before and after the formation of each nation state. The special issue includes contributions that spotlight identity constructions based on class, religion, gender, monarchy, empire, transnational entanglements, cosmopolitanism, and regional particularism. By comparing Italian and German case studies, we will address subjects of high and soft politics (pantheons, museums, opera) as well as working-class sensibilities and religious minorities. How do they interact with ideas of national independence and ethnic identity? This approach enables us to move beyond national narratives and their state-centred view, rethinking the rise of nationalism within a broader framework of non-national, multiple, hybrid, or marginal group identities.